The Implementation of Multiple-Representation Approaches Based on E-Module to Reduce Misconceptions of Prospective Physics Teachers During the Covid-19 Pandemic - Ahmad Busyairi; Aris Doyan; Ahmad Harjono; Sutrio Sutrio; I Wayan Gunada (Postgraduate, University of Mataram, 2021)
One of the problems that are often found in universities, especially in physics subjects, is the existence of misconceptions in students (learners). This study aims to determine the effectiveness of using the multiple-representation approach Based on E-Module in reducing the misconceptions of prospective physics teachers during the Covid-19 pandemic. The method used is quantitative research with a one-group pretest-posttest design. The sample consisted of 25 prospective physics teachers at one of the universities in the city of Mataram. The instrument used in this research is an open-ended three-tier test. A total of 10 test items with 30 questions were used in this study. The test was given twice, namely before and after treatment. The test results data were then analyzed using descriptive statistics to determine the decrease in the percentage of students who experienced misconceptions. Based on the results of data analysis shows that there is a decrease in the percentage of students who experience misconceptions by 31.89% from the initial number of 57.19 to 25.30%. This decrease in misconceptions was also followed by an increase in the percentage of students who understood the concept from 18.14 to 72.38%. Thus, it can be concluded that the application of the multiple representation approach assisted by E-Modules can be used as an alternative to reduce misconceptions and improve understanding of the concept of prospective physics teachers in the COVID-19 pandemic